The Limits of Electronic Fetal Heart Rate Monitoring in the Prevention of Neonatal Metabolic Acidemia. Issue 4 (December 2017) - Clark, S.L.; Hamilton, E.F.; Garite, T.J.; Timmins, A.; Warrick, P.A.; Smith, S.
Abstract : ( Am J Obstet Gynecol . 2017;216(2):163.e1–163.e6) While unexpected intrapartum fetal death has largely been eliminated with the use of electronic fetal heart rate monitoring (EFHRM), the goal of consistently preventing hypoxia-induced fetal metabolic acidemia has proven difficult. Moreover, the impact of EFHRM on long-term neonatal outcomes is not well documented, as the potential impact of monitoring conditions on outcomes with multifactorial origins (such as cerebral palsy) is so small as never to have been statistically demonstrated. The present outcomes-blinded case control study had 3 aims: to determine why infants were born with significant metabolic acidemia despite the use of EFHRM, to evaluate the potential impact of a previously published algorithm on these outcomes, and to consider the limits of EFHRM in the prevention of neonatal metabolic acidemia.